2018
DOI: 10.1039/c7sc04798c
|View full text |Cite
|
Sign up to set email alerts
|

Cell imaging of dopamine receptor using agonist labeling iridium(iii) complex

Abstract: A long-lived complex 13 could selectively bind to dopamine receptors (D1R/D2R) and monitor their internalization in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…The success of metal complexes such as platinum (Pt) complexes for anticancer applications encourages the development of new metallodrugs . Recent fundamental research and clinical trials showed that ruthenium (Ru) complexes are promising alternatives for Pt drugs .…”
Section: Introductionmentioning
confidence: 99%
“…The success of metal complexes such as platinum (Pt) complexes for anticancer applications encourages the development of new metallodrugs . Recent fundamental research and clinical trials showed that ruthenium (Ru) complexes are promising alternatives for Pt drugs .…”
Section: Introductionmentioning
confidence: 99%
“…As a GPCR (G protein-coupled receptor) member, DR is classified into D1-like (including DRD1 and DRD5) and D2-like (including DRD2, DRD3 and DRD4) families according to their coupled G proteins, Gαs or Gαi [ 17 , 18 ]. Many neurogenic diseases such as Parkinson and Alzheimer’s disease were associated with DR dysfunction and relevant agonists or antagonists are used to target DR for therapy or modified to generate effective probes for live imaging [ 19 , 20 , 21 , 22 , 23 ]. Since Zhang et al reported that compounds with affinity for DRs could modulate autophagy in a screen [ 24 ], functions of different DRs agonists and antagonists in autophagy have been examined in cells and animals [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This considerably increases image resolution in luminescence microscopy and lowers detection threshold in sensing experiments. 1,4,11,12 As a result, advanced sensing platforms were developed to recognize various biologically relevant analytes, including (but not limited to) detection of cyanide ions, 13 biothiols 14 (including thiourea 15 ), b-galactosidase, 16 dopamine receptor, 17 or inhibitor of tumor necrosis factor-a. 18 Moreover, the sensitivity of emission parameters (intensity and lifetime) to oxygen concentration makes possible mapping of oxygen concentration in in vitro and in vivo experiments, 19,20 including quantitative measurements with the use not only emission intensity but also phosphorescence lifetime imaging (PLIM) techniques, [21][22][23][24][25] which provides considerably higher precision in oxygen biodistribution mapping.…”
Section: Introductionmentioning
confidence: 99%